Shalat Tahajjud Sebagai Penguatan Karakter Etika Konselor Islami - Adinda Sinta Ismail; Akhir Pardamean Harahap; Hamdi Halomoan Hasibuan; Nanda Nur Sakinah (Peneliti.net, 2023)
In Islam prayer is something that is fundamental, sacred so that it is something that must be carried out by Muslims. Tahajjud prayer, sunnah prayer which has extraordinary benefits, so that many Muslims still actively raise the midnight prayer in the midst of sleepiness holding their eyes. The purpose of this research is to find out whether the midnight prayer is able to have a good effect on the character of Islamic counselors, where we know the midnight prayer is able to change a person's lifestyle to become religious and regular. The research method used is the library study method, in which the research procedure collects reference material from various references in the form of books, journals, etc. The results of his research are that the magic of the midnight prayer is able to change the character of an individual or counselor to become a more conducive and religious person, and the midnight prayer is also a stronghold of faith, so it is very important to carry it out at midnight. The conclusion is to help someone better understand, care for, and act on a core foundation of ethical values, to improve character and add to the privileges of the midnight prayer.